Medium-specific escape motivation in internet gaming disorder and problematic social media use among Chinese university students: the role of self-control - Zinan Wang; Lihui Ren; Ruoyu Zhou; Limin Wu; Yuan Liang; Ying Zhang; Yirui Wang (Frontiers in Public Health, 2026)
Background Escape motivation is a well-established correlate of problematic technology use, but it is commonly measured as a general tendency. This cross-sectional study examined whether escape motivation tied to a particular medium shows differential associations with problems in that medium and examined the role of self-control. Methods A total of 358 Chinese university students (232 women; mean age 20.2 years) completed measures of game and short-video escape motivation, self-control, internet gaming disorder (IGD) symptoms, problematic social media use (PSMU), and relevant covariates. The primary regression model simultaneously entered both escape motivations and adjusted for sex, age, and daily gaming time; minimally adjusted and stringent models were treated as sensitivity analyses. Results In the primary model, game escape motivation was associated with IGD symptoms ( β = 0.34, p < 0.001), whereas short-video escape motivation was not ( β = 0.01, p = 0.872); the coefficient difference was significant (Wald p = 0.015). Short-video escape motivation was associated with PSMU ( β = 0.31, p < 0.001), whereas game escape motivation was not ( β = 0.09, p = 0.216), but the coefficient-difference test was non-significant (Wald p = 0.133). The short-video association weakened to non-significance under stringent adjustment. Self-control was negatively associated with both outcomes, while moderation evidence was limited and exploratory. Conclusion The game escape–IGD association was robust, whereas the short-video escape–PSMU association remains preliminary. These cross-sectional results do not establish causal, screening, or preventive effects.